SlideSpace: Heuristic Design of a Hybrid Presentation Medium - Edge, Darren; Yang, Xi; Kotturi, Yasmine; Wang, Shuoping; Feng, Dan; Lee, Bongshin; Drucker, Steven (ACM Transactions on Computer-Human Interaction, 2016)
The Slide and Canvas metaphors are two ways of helping people create visual aids for oral presentations. Although such physical metaphors help both authors and audiences make sense of material, they also constrain authoring in ways that can negatively impact presentation delivery. In this article, we derive heuristics for the design of presentation media that are independent of any underlying physical metaphors. We use these heuristics to craft a new kind of presentation medium called SlideSpace—one that combines hierarchical outlines, content collections, and design rules to automate the real-time, outline-driven synthesis of hybrid Slide-Canvas visuals. Through a qualitative study of SlideSpace use, we validate our heuristics and demonstrate that such a hybrid presentation medium can combine the advantages of existing systems while mitigating their drawbacks. Overall, we show how a heuristic design approach helped us challenge entrenched physical metaphors to create a fundamentally digital presentation medium with the potential to transform the activities of authoring, delivering, and viewing presentations.